2014
DOI: 10.1016/j.exppara.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Physical exercise protects myenteric neurons and reduces parasitemia in Trypanosoma cruzi infection

Abstract: To evaluate the parasitemia, nitrergic neurons, and cytokines in Trypanosoma cruzi-infected mice subjected to moderate physical exercise, forty male Swiss mice, 30days of age, were divided: Trained Control (TC), Trained Infected (TI), Sedentary Control (SC), and Sedentary Infected (SI). The moderate physical exercise program on a treadmill lasted 8weeks. Three days after completing the moderate physical exercise program, the TI and SI groups were inoculated with 1300 blood trypomastigotes of the Y strain of T.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 25 publications
1
9
0
3
Order By: Relevance
“…Histopathological evaluation showed differences in the inflammatory infiltrate, which was observed to be lower in the trained group. Similar results on the effects of physical exercise in chagasic animals were obtained in the enteric nervous system (Moreira et al, 2013, 2014a,b). The direct actions of the parasite in the cardiac muscle in the above parameters have not been previously reported in the literature.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Histopathological evaluation showed differences in the inflammatory infiltrate, which was observed to be lower in the trained group. Similar results on the effects of physical exercise in chagasic animals were obtained in the enteric nervous system (Moreira et al, 2013, 2014a,b). The direct actions of the parasite in the cardiac muscle in the above parameters have not been previously reported in the literature.…”
Section: Discussionsupporting
confidence: 75%
“…Moderate physical exercise (ET) contribute to the preservation of nitrergic (Moreira et al, 2014b) and colonic myenteric (Moreira et al, 2013, 2014a) neurons during T. cruzi infection. Pre-infection ET induced some improvement toward the immune response to T. cruzi infection in mice (Schebeleski-Soares et al, 2009) and rats (Novaes et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nowadays, this expression can be defined as the field of the biomedical science that studies the interference of physical exercise in both induction and regulation of immune response and that is why exercise immunology is an essential subject for both physical education and immunology communities (Bortolini et al, 2013). Several studies concerning physical exercise found plenty improvements in immune system (Walsh et al, 2011a,b) and recent experimental works have reinforce its importance during various processes, as follows: (a) to fight cancer (Almeida et al, 2009), or protect graft (Fiuza-Luces et al, 2013) (b) to improve the clearance of pathogens, e.g., Trypanosoma cruzi (Schebeleski-Soares et al, 2009; Moreira et al, 2014); and (c) to promote regulation of cytokines as IFN-γ, TNF, TGF-β1, IL-4, IL-10, and IL-12 during infection by Leishmania (Terra et al, 2013), as well as regulation of TNF (Chao et al, 1992) or TNF and TGF-β (Moreira et al, 2014), during Toxoplasma gondii and T. cruzi infection, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…As mudanças da população neuronal do plexo mioentérico já foram bem estudadas com a cepa Y de T. cruzi (CAMARGOS et al, 2000;MAIFRINO et al, 1999;MOREIRA et al, 2011;MOREIRA et al, 2013;MOREIRA et al, 2014a;MOREIRA et al, 2014b;NOGUEIRA-PAIVA et al, 2014). No entanto, nenhum estudo com a cepa CL foi realizado para verificar as alterações morfoquantitativas causadas no plexo mioentérico.…”
Section: Introductionunclassified